Profil Berolahraga Mahasiswa Universitas Negeri Semarang Pada Era Kebiasaan Baru Pasca Pandemi Covid-19 - Ade Reza Sofani; Said Junaidi (Indonesian Journal of Kinanthropology (IJOK), 2023)
Background: The Covid-19 pandemic has affected sports activities in the community, especially Semarang State University students. The purpose of this research is to find out the profile or state of exercise of Semarang State University students class of 2018 with the principles of FITT (Frequency, Intensity, Type, and Time) and goal in exercise. Methods: This type of research is descriptive quantitative. The population in this study were all 2018 UNNES students. The sampling technique was random sampling, the number of samples used was 368. The research instrument used the Global Physical Activity Questionnaire (GPAQ). Data analysis techniques using descriptive statistics and percentages. Results: The results of the analysis showed that 71.70% exercised at a frequency of 3-5 times, the intensity of light and moderate exercise was 88.60% and 82.30%, the duration of 31-45 minutes was 71.20%. The aim of exercising is to reduce stress by 87.80% and increase body immunity by 86.40% during the era of new habits after the Covid-19 pandemic Conclusions: Based on the results of the study it can be concluded that Semarang State University students class of 2018 have exercised according to the FITT.